2005
DOI: 10.5194/angeo-23-2347-2005
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer structure of mid-latitude sporadic-<i>E</i> observed during the SEEK-2 campaign

Abstract: Abstract. In the mid-latitude ionospheric region, sporadic-E layers (E s layers) have often been observed, revealing multiple layers. The E s layers observed during the SEEK-2 rocket campaign showed double electron density peaks; namely, there are stable lower peaks and relatively unstable upper peaks. We examined the effects of wind shear and the electric fields on the generation of the multiple layer structure, in comparison with the electron density profile, the neutral wind, and the DC electric field obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…This campaign, along with SEEK-1, confirmed that the QP echoes are associated with Es-layers mainly around 105 km. Accumulation of the E-region plasma into the layers is well explained by the shear of the neutral wind (Bernhardt et al, 2005;Larsen et al, 2005;Pfaff et al, 2005;Wakabayashi and Ono, 2005;Yokoyama et al, 2005). The Es-layers are spatially modulated by the motion of the neutral atmosphere (Maruyama et al, 2006), and then FAI echoes start to appear.…”
mentioning
confidence: 99%
“…This campaign, along with SEEK-1, confirmed that the QP echoes are associated with Es-layers mainly around 105 km. Accumulation of the E-region plasma into the layers is well explained by the shear of the neutral wind (Bernhardt et al, 2005;Larsen et al, 2005;Pfaff et al, 2005;Wakabayashi and Ono, 2005;Yokoyama et al, 2005). The Es-layers are spatially modulated by the motion of the neutral atmosphere (Maruyama et al, 2006), and then FAI echoes start to appear.…”
mentioning
confidence: 99%
“…These factors result in variations of E s occurrence with respect to local time, altitude, latitude, longitude, and season (Haldoupis, 2011). Furthermore, in the high-latitude region, the occurrence of E s is more significantly influenced by the local electric field rather than the wind shear due to the geomagnetic field difference (Wakabayashi and Ono, 2005). Please note that the term E s is now widely used to represent the inhomogeneity of the ionospheric E layer (e.g., layers, cloud, irregularity) rather than only the echo trace from the ionogram when it was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…They could lift up part of the E s layer to overlap with the original layer. Based on the SEEK-2 rocket campaign observations, Wakabayashi and Ono (2005) analyzed the double-peak E s layer phenomena in detail. They found that the lower peak is usually more stable than the upper peak.…”
Section: Introductionmentioning
confidence: 99%
“…There can be a few such regions of lower thermospheric heights where heavy metalic ions can be forced to form multiple layers (e.g. see Turunen et al, 1993;Hocke et al, 2001;Damtie et al, 2002;Wakabayashi and Ono, 2005, and references therein; .…”
Section: Atmospheric Shear Wavesmentioning
confidence: 99%